MODEL KELELAHAN EMOSIONAL: ANTASEDEN DAN DAMPAKNYA TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASI DOSEN - Siti Mujiatun; jufrizen jufrizen; Pandapotan Ritonga (Universitas Mercu Buana, 2019)
The general objective of this research is formulating a model of emotional exhaustion, job satisfaction and organizational commitment of lecturers in private higher education institutions in Medan. The research was conducted at the Islamic University of Sumatera Utara, University of Muhammadiyah Sumatera Utara, Panca Budi University, Dharmawangsa University, Al-Azhar University, Muslim Nusantara University, Al Washliyah University, Prima Indonesia University, HKBP Nommensen University, Potensi Utama University, and Sari Mutiara University. This research is causality research with all permanent lecturers of private higher education institutions in Medan as a population. Data collection was using interviews and questionnaires. Structural Equation Model is the data analysis used in this research. The results showed that leadership has an effect on emotional exhaustion and organizational commitment of lecturers. Then, self-efficacy and emotional exhaustion respectively affect job satisfaction and organizational commitment of lecturers while job satisfaction only affects the organizational commitment of lecturers in private higher education institutions in Medan